Role of inflammation and oxidative stress in endothelial progenitor cell function and mobilization: therapeutic implications for cardiovascular diseases. - Tousoulis, D; Andreou, I; Antoniades, C; Tentolouris, C; Stefanadis, C (2008)
Endothelial progenitor cells (EPCs) are mobilized from the bone marrow into the peripheral circulation, home to sites of injury, and incorporate into foci of neovascularization, thereby improving blood flow and tissue recovery. Patients with cardiovascular diseases, including coronary artery disease, heart failure, hypertension, and diabetes, have been shown to exhibit reduced number and functional capacity of EPCs. Considerable evidence indicates that EPCs constitute an important endogenous system to maintain endothelial integrity and vascular homeostasis, while reduced number of EPCs has recently been shown to predict future cardiovascular events. Thus, enhancement of EPCs could be of potential benefit for individuals with cardiovascular diseases. The interplay between inflammation and oxidative stress is involved in the initiation, progression, and complications of cardiovascular diseases. Emerging evidence from in vitro and clinical studies suggests that inflammatory and oxidative changes influence EPC mobilization. Drugs with anti-inflammatory and antioxidant properties, currently administered to patients with cardiovascular diseases, such as statins, have been demonstrated to exert beneficial effects on EPC biology. A better understanding of the inflammatory and oxidative mechanisms leading to the numerical and functional impairment of EPCs would provide additional insight into the pathogenesis of cardiovascular disease and create novel therapeutic targets.